The Role of Management Accounting Systems in Supporting Entrepreneurial Decision-Making in Cambodia - Lim, Na (PT. Batari Edu Calya, 2026)
This study investigates the critical role of management accounting systems (MAS) in facilitating entrepreneurial decision-making within the Cambodian business context. As entrepreneurship emerges as a pivotal strategy for economic development and employment generation in developing economies, understanding the informational infrastructure that supports entrepreneurial ventures becomes increasingly essential. Management accounting systems serve as fundamental suppliers of economic information that enable entrepreneurs to make informed decisions regarding business operations, resource allocation, and strategic planning. This research synthesizes existing literature on accounting information systems and their influence on entrepreneurial behavior, examining how the integration of financial and managerial accounting components provides comprehensive decision-support mechanisms. The findings reveal that accounting information systems significantly and positively influence entrepreneurial decision-making by providing reliable information management capabilities, enhancing business operation oversight, and supporting strategic resource deployment. Furthermore, the study demonstrates that the quality of accounting information systems, when combined with digital technologies such as e-commerce platforms, creates synergistic effects that amplify entrepreneurial confidence and decision-making efficacy. The implications for Cambodia's developing entrepreneurial ecosystem suggest that strengthening management accounting education and system implementation could substantially enhance the nation's entrepreneurial capacity and economic growth trajectory.